Investigating the relationship between psychological vulnerability and psychological performance of female soccer players - Çutuk Selman; Çutuk Zeynep Akkuş; Ünal Hakan (SHS Web of Conferences)
This study aimed to investigate the relationship between psychological vulnerability and psychological performance among female soccer players. The sample comprised 129 voluntary female athletes competing in the 2nd and 3rd Leagues organized by the Turkish Football Federation. Data were collected using the Psychological Vulnerability Scale and the Psychological Performance Inventory. The analysis employed descriptive statistics, the Pearson Correlation Coefficient, and Structural Equation Modelling (SEM). The findings revealed a significant negative relationship between psychological vulnerability and several subdimensions of the psychological performance inventory, including selfconfidence, negative energy, attention control, motivation level, positive energy, and attitude control. However, no significant relationship was observed with the sub-dimension of visualization and imagery control. Furthermore, the structural equation modelling indicated that psychological vulnerability serves as a significant predictor of the subscales for selfconfidence, negative energy, and motivation level within the psychological performance inventory